Investigation of potential efficacy of nanospanlastic vesicular drug delivery system for targeting the brain: formulation, characterization, and in-vivo studies - Patel, Ashwini; Pandey, Prachi (Journal of Applied Pharmaceutical Research, 2025)
Background: Edaravone, a potent antioxidant, has limited brain bioavailability due to poor solubility and restricted permeability across the blood-brain barrier (BBB). Intranasal delivery offers a promising alternative for brain targeting by bypassing the BBB. Objective: To develop and evaluate a nanospanlastic-based in-situ nasal gel formulation of edaravone for enhanced brain delivery. Methodology: A Quality by Design (QbD) approach was employed to identify and optimize critical formulation variables using Plackett-Burman and Central Composite Design. The optimized nanospanlastics were incorporated into a gellan gum-based ion-activated in-situ nasal gel and characterized through in vitro, ex vivo, and in vivo studies. Results and Discussion: The optimized formulation exhibited a particle size of 213.4 nm, a drug entrapment efficiency of 67.59%, and rapid gelation upon contact with nasal fluid. In vitro diffusion showed over 80% drug release within 30 minutes, while ex vivo studies confirmed improved permeation (flux: 7.8067 µg/cm²/hr). Histopathology revealed no nasal mucosal irritation. Pharmacokinetic studies in rats demonstrated significantly enhanced brain and plasma exposure compared to the marketed edaravone injection, with higher Cmax (78.73 ng/mL), Tmax (121.2 min), and AUC. Conclusion: The developed nanospanlastic-based nasal gel offers a non-invasive, effective strategy for brain delivery of edaravone, with potential to improve therapeutic outcomes in neurological disorders.